Production and Characterization of Polyclonal Anti-idiotypic Antibody to Malaria Merozoite Antigen - Jiraporn Suwan; Chakrit Hirunpetcharat; Prachya Kongtawelert (Journal of Associated Medical Sciences, 2015)
-